3-(x-5)=y+2
2(X+y)=4-3y
Answers
Answered by
0
Step-by-step explanation:
this is your answer maths
Attachments:
![](https://hi-static.z-dn.net/files/d33/eaf37c2590ce03ef68489205ad97e76b.jpg)
Answered by
3
Answer:
y = -8/3
Step-by-step explanation:
3-(x-5)=y+2
3-x+5 = y+2
8-x = y+2
x+y = 6
2(X+y)=4-3y
12 = 4-3y
3y = -8
y = -8/3
Similar questions
Computer Science,
6 months ago
Biology,
6 months ago
Math,
6 months ago
Art,
1 year ago
English,
1 year ago
Math,
1 year ago
Geography,
1 year ago
Computer Science,
1 year ago